Establishing Cell Models to Understand Cellular Toxicity: Lessons Learned from an Unconventional Cell Type - Tino Vollmer; Bernd Stegmayr (Toxins, 2022)
The syndrome of uremic toxicity comprises a complex toxic milieu in-vivo, as numerous uremic substances accumulate and harm the organ systems. Among these substances, toxic and non-toxic players differently interfere with human cells. However, results from animal experiments are not always compatible with the expected reactions in human patients and studies on one organ system are limited in capturing the complexity of the uremic situation. In this narrative review, we present aspects relevant for cellular toxicity research based on our previous establishment of a human spermatozoa-based cell model, as follows: (i) applicability to compare the effects of more than 100 uremic substances, (ii) detection of the protective effects of uremic substances by the cellular responses towards the uremic milieu, (iii) inclusion of the drug milieu for cellular function, and (iv) transferability for clinical application, e.g., hemodialysis. Our technique allows the estimation of cell viability, vitality, and physiological state, not only restricted to acute or chronic kidney toxicity but also for other conditions, such as intoxications of unknown substances. The cellular models can clarify molecular mechanisms of action of toxins related to human physiology and therapy. Identification of uremic toxins retained during acute and chronic kidney injury enables further research on the removal or degradation of such products.